Human culture and its interpretation from the organizational culture perspective (2011)
This article exposes a view point beyond a mere observation of an organizationalreality and practice at hand. It engages the subject of human culture as a referenceto find an explanation of the staff’s behavior in the companies. Likewise, to makecomparisons of the staff’s behavior by using the administrative theory called “theorganizational culture”. More specific, the main objective of this article more thandoing a rigorous academic tracking is the conceptualization of human culture bythe administration based on the theory.